Analisis Perancangan Dan Implementasi Sistem Informasi Stationary Berbasis Web Pada PT. Indako Trading Coy - Giovanni Chairis; Ade Maulana (Journal Information System Development (ISD), 2022)
PT. Indako Trading Coy is a company engaged in the automotive sector, which in carrying out business processes must use ATK. The company has problems in the procurement process and ATK requests where the process is still done manually and offline. Data collection in this research can be done by using interview techniques, literature study, observation, problem analysis and questionnaires to several users related to the system, then the author designs a Web-based stationary information system. From the results of the implementation of the information system, it can be proven that the procurement of ATK, ATK requests, calculation of ATK stock and forming a report becomes faster and more correct. and can be proven through data obtained from 12 questions conducted through a questionnaire that has 5 answer points to 10 users of the stationary information system. Based on the results of the questionnaire, it can be shown that the success of the system is 91.83% with an average point value of 91.83 points from user statements, it can be concluded that users strongly agree that this stationary information system can help the process of supplying stationery, requesting stationery, calculating stock of stationery and form reports quickly and correctly